Penyuluhan Pemeliharaan Ayam Broiler yang Rendah Kolesterol dengan Pemberian Suplemen di Desa Banglas, Kabupaten Kepulauan Meranti - Almandra; Delia Meldra; Albertus L. Setyabudhi (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
In the village of Banglas, Meranti Islands, there are poultry farmers, namely broiler chickens, who supply the chickens to markets in the Meranti Islands area. However, the problem faced by farmers is that the number of chicken seeds with chickens ready to sell is far lower than the number of initial seeds. Based on the importance of this, counseling on the maintenance of low-cholesterol broiler chickens by providing supplements in Banglas Village, Meranti Islands Regency. In this outreach activity, the instructor provides information on the importance of giving probiotics to farm chickens so that the risk of dead seeds before being sold can decrease the number, then the extension worker provides supplements and provides supplements to farmers. After giving supplements and being monitored for three months, it was found a decrease in the mortality rate of the broiler chickens.